Answer:
5x-(x+3)=(3x+6)-5
We move all terms to the left:
5x-(x+3)-((3x+6)-5)=0
We get rid of parentheses
5x-x-((3x+6)-5)-3=0
We calculate terms in parentheses: -((3x+6)-5), so:
(3x+6)-5
We get rid of parentheses
3x+6-5
We add all the numbers together, and all the variables
3x+1
Back to the equation:
-(3x+1)
add all the numbers together, and all the variables
4x-(3x+1)-3=0
get rid of parentheses
4x-3x-1-3=0
add all the numbers together, and all the variables
x-4=0
move all terms containing x to the left, all other terms to the right
x=4
Explanation: